1998
DOI: 10.1046/j.1440-1754.1998.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Young people with spina bifida: Transfer from paediatric to adult health care

Abstract: An expectation of health care for young people with disability is that quality coordinated care continues to be available as they pass from the paediatric to the adult health care system. While individual clinicians provide this service well, the widespread absence of coordinated multidisciplinary care for young people with spina bifida in the adult health care system is a major deficiency. This paper describes the planning and implementation that underpinned the transfer of 10 young people with spina bifida f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 11 publications
2
50
0
Order By: Relevance
“…Similar to other cohorts, many participants (almost 50%) in this study were dependent on their carers for management and support [34]. The positive effects on various aspects of bladder/bowel and cognitive/behaviour function in this study are also reported in different SB subgroups and settings [3,4,13,14,35,36]. The improvements in bladder/bowel dysfunction, cognitive and other outcomes (QoL, coping strategies) were independent of study participants' demographic and clinical characteristics, which suggest the need to further engage pwSB in rehabilitation activities.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to other cohorts, many participants (almost 50%) in this study were dependent on their carers for management and support [34]. The positive effects on various aspects of bladder/bowel and cognitive/behaviour function in this study are also reported in different SB subgroups and settings [3,4,13,14,35,36]. The improvements in bladder/bowel dysfunction, cognitive and other outcomes (QoL, coping strategies) were independent of study participants' demographic and clinical characteristics, which suggest the need to further engage pwSB in rehabilitation activities.…”
Section: Discussionsupporting
confidence: 79%
“…Although several studies in the paediatric population demonstrate effectiveness of a coordinated ID approach to management, this does not extend to adults and there is lack of comprehensive ambulatory care models [11][12][13]. The aim of this study, therefore, was to assess the effectiveness of a structured ID rehabilitation intervention to improve disability and participation in an adult SB population in an Australian community cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have described the process of transition in their programs. 9,12 Moreover, few studies have assessed, empirically, the impact of this transition to adult-centered health care in terms of health care outcomes.2 The purpose of this pilot study is to evaluate the health care access and utilization in the Jacksonville, Florida, area of young adults with spina bifida (YASBs) after transfer to adult abbreviations JaxHATS = Jacksonville Health and Transition Services; QOL = quality of life; SB = spina bifida; SDC = Spinal Defects Clinic; UF = University of Florida; WCH = Wolfson Children's Hospital; YASB = young adult with spina bifida. submitted January 5, 2015. obJective The transition of the young adult with spina bifida (YASB) from pediatric to adult health care is considered a priority by organized pediatrics.…”
mentioning
confidence: 99%
“…Few studies have described the process of transition in their programs. 9,12 Moreover, few studies have assessed, empirically, the impact of this transition to adult-centered health care in terms of health care outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation